Recent advances in PCR-free nucleic acid detection for SARS-COV-2 - Ma, Xiaowei; Xu, Jingsong; Zhou, Fei; Ye, Jing; Yang, Donglei; Wang, Hua; Wang, Pengfei; Li, Min (Frontiers in Bioengineering and Biotechnology, 2022)
As the outbreak of Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory disease coronavirus 2 (SARS-COV-2), fast, accurate, and economic detection of viral infection has become crucial for stopping the spread. Polymerase chain reaction (PCR) of viral nucleic acids has been the gold standard method for SARS-COV-2 detection, which, however, generally requires sophisticated facilities, laboratory space, and is time consuming. This review presents recent advances in PCR-free nucleic acid detection methods for SARS-CoV-2, including emerging methods of isothermal amplification, CRISPR, electrochemistry, Raman spectroscopy.